Univex Interval-Valued Mapping with Differentiability and Its Application in Nonlinear Programming - Lifeng Li; Sanyang Liu; Jianke Zhang (Journal of Applied Mathematics)
Interval-valued univex functions are introduced for differentiable programming problems. Optimality and duality results are derived for a class of generalized convex optimization problems with interval-valued univex functions.